Imperfect Financial Markets, External Debt, and the Cyclicality of Social Transfers - Maren Frömel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper deals with fiscal policy over the business cycle when international financial markets are imperfect. I document evidence that government expenditure tends to be more procyclical the higher is the borrowing cost for a sovereign. Decomposing government expenditure components shows that the cyclical correlations of government social transfers are the most important components driving cross-country differences in the behavior of government spending over the business cycle. I build a simple model of optimal fiscal policy in the presence of income inequality where government spending is financed by costly taxation and by external debt in form of a risk free bond. Government spending consists of a public good which provides direct utility, and of social transfers that can be targeted towards low income agents. When additional frictions are in the form of exogenous borrowing constraints, the government runs a procyclical tax and transfer policy in the neighbourhood of the constraint and a counteryclical policy when asset or debt holdings are not close to the constraint. The need to smooth both aggregate consumption and tax cost over the business cycle deliver the qualitative difference in transfer policy when the government cannot borrow enough. The procyclicality of transfers is stronger the tighter is the borrowing constraint in this model. In contrast, government spending on public goods is always procyclical. The results implied by the theoretical model are qualitatively consistent with the data and emphasize the need to decompose government expenditure to understand fiscal procyclicality.
Keywords: E62; F34; F41; 330